Adolescent development and justice; bridging science with practice: how should the legal system respond to juveniles charged with homicide? : a developmental perspective - Sbeglia, Colleen (The Routledge international handbook of juvenile homicide, 2024)
This chapter provides a broad discussion of the developmental factors related to juvenile homicide. We aim to bridge science with practice by providing a summary of the scientific work on brain and socioemotional development during adolescence, the developmental factors that may contribute to serious antisocial behavior (including homicide), the developmental factors that may promote rehabilitation, the developmental mitigating factors, and other legal considerations for juveniles convicted of homicide. All things considered, there is likely no one-size-fits-all approach to dealing with juveniles who have committed murder. Ultimately, the chapter discusses the unique challenges facing legal decision makers, given the need to hold juveniles accountable in a developmentally appropriate way while also providing justice for victims.